Indirect comparison of clobazam and other therapies for Lennox–Gastaut syndrome. (15th February 2013) - Cramer, J. A.; Sapin, C.; François, C.
<x xml:space="preserve">Abstract</x> Objective In the absence of head‐to‐head trials, it is not feasible to make direct comparisons of antiepileptic therapies for the treatment of Lennox–Gastaut syndrome (LGS). We conducted indirect comparisons of the relative efficacies of clobazam, felbamate, lamotrigine, topiramate, and rufinamide as adjunctive treatments for LGS. Methods Clinical studies of LGS patients were identified in a 2009 Cochrane review and by electronic database search. Five randomized controlled trials were included in this systematic review, which reports findings from indirect comparisons between clobazam and other approved adjunctive LGS therapies (felbamate, lamotrigine, topiramate, rufinamide) in the United States and Europe. As outcomes were not uniformly reported across studies, the primary efficacy endpoint from each trial was transformed into Cohen's d effect size, to facilitate indirect comparisons. Typical interpretations of Cohen's d results are as follows: d < 0.2, change not detectable; 0.2 ≤ d < 0.5, small change; 0.5 ≤ d < 0.8, moderate change; and 0.8 ≤ d, large change. Results High‐dosage clobazam (1.0 mg/kg/day) was found to have the strongest treatment effect vs placebo (effect size 0.80), with moderate effects (effect sizes >0.50) for medium‐dosage clobazam (0.5 mg/kg/day) and rufinamide. Felbamate, lamotrigine, and topiramate had low effect sizes. Indirect comparisons of numbers of total seizures and tonic–atonic seizures ('drop attacks') demonstrated superiority of both clobazam dosages over all comparators. Conclusions High‐ and medium‐dosage clobazam was estimated to be more efficacious than other LGS treatments. Our analysis relied on published data and could not draw on direct head‐to‐head data of clobazam with alternatives. Further comparative research is ongoing to assess the usefulness of clobazam for LGS.